Pengaruh Thin Capitalization dan Transfer Pricing Aggressiveness terhadap Penghindaran Pajak dengan Financial Constraints sebagai Variabel Moderasi - Melina Fajrin Utami; Ferry Irawan (Owner : Riset dan Jurnal Akuntansi, 2022)
The purpose of this study was to determine the effect of thin capitalization, transfer pricing aggressiveness on tax avoidance with financial constraints as moderating variable. This study used a quantitative approach with population with sample of manufacturing companies listed on the Indonesia Stock Exchange from 2016 to 2019. The sampling technique used purposive sampling and obtained 72 companies as samples. This study used panel data and the analysis was multiple linear regression and interaction regression. The results show that thin capitalization, transfer pricing aggressiveness, and financial constraints have a positive effect on tax avoidance. Further research shows that financial constraints strengthen the effect of thin capitalization on tax avoidance, but financial constraints do not moderate the effect of transfer pricing aggressiveness on tax avoidance.